Immunological indicators of complications of surgical bowel disease in children - D. A. Musakhodjayeva; R. K. Karimov; S. Kh. Rasulova (Медицинская иммунология, 2023)
The article is devoted to the development of immunological indicators of intestinal inflammation in children, which is of great importance for health authorities when organizing specialized pediatric and surgical services. The proposed method contributes to the early diagnosis and prevention of complications of inflammatory surgical bowel diseases in children, which is of great practical importance. The purpose of the study: To develop immunological indicators of complications of surgical bowel diseases in children. A retrospective analysis of 867 case histories of children who received inpatient treatment at the Department of Pediatric Surgery of the Bukhara branch of the Republican Scientific Center of Emergency Medical Care from 2019 to 2022 for surgical diseases of the gastrointestinal tract was carried out. The authors conducted an immunological study of 91 pediatric patients. All children underwent immunological blood tests: cellular and humoral immunity, cytokines (TNFα, IFNα, IL-8, MCP-1 and vascular endothelial growth factor VEGF-A) were studied. For the prevention of postoperative complications of CKD in children, it is recommended to determine IFNα in the blood serum in the period before surgery to solve the indications for immunocorrection. A noticeable positive relationship was established between IFNα and CD8 – r = 0.34, between IFNα and CD23 – r = 0.38, between IFNα and IgA – r = 0.39, between IFNα and PCT – r = 0.36. At the same time, PCT has a noticeable negative relationship with CD16 – r = -0.31 and with CD8 – r = -0.31 against the background of a noticeable positive relationship with IgG – r = 0.32 and IFNα – r = 0.36. It was found that IFNα is a more informative indicator of the effectiveness of the immune response, and PCT is an indicator of the effectiveness of antibacterial therapy in surgical bowel diseases in children